Behavior of large piled-raft foundation on clay soil. (1st February 2018) - Mali, Shivanand; Singh, Baleshwar
Abstract: The piled-raft foundation is usually adopted to support the offshore structures. In the present study, a large piled-raft has been simulated numerically through 3-D finite element modeling. The objective of the present study was to investigate the effect of pile spacing, pile length, pile diameter and raft-soil stiffness ratio on the settlement, load-sharing, bending moments, and shear force behavior of large piled-raft foundation. The results indicated that with increase in pile spacing up to the 5 to 6 times of the pile diameter, both average settlement ratio and differential settlement ratio decreased effectively and thereafter it increased gradually. Raft with smaller raft-soil stiffness ratio and larger pile group to raft width ratio observed to be effective in decreasing the average settlement ratio. The load-sharing ratio decreased with increase in pile spacing whereas; it increased with increase in pile length. With increase in pile spacing, bending moment ratio increased and as the length of pile increased bending moment ratio decreased up to pile group to raft width ratio of 0.6 and thereafter it increased. Highlights: For any pile group to raft width ratio, with increase in pile spacing to diameter ratio, average settlement ratio, differential settlement ratio, and bending moment ratio decrease up to the pile spacing of 6 times the pile diameter and then increases. A raft with smaller raft-soil stiffness ratio and larger pile group to raft width ratio is observed to be effective in decreasing the average settlement. With increase in pile length to diameter ratio, bending moment ratio decrease up to B g / B r  = 0.6 and thereafter it increases, whereas shear force ratio increases linearly. The raft and pile group in piled-raft has carried lesser loads as that of unpiled raft and free standing pile groups. The maximum bending moment and maximum shear force in the raft increases as the raft-soil stiffness ratio increases.